PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN ASING, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014) - Nur Asiah; Said Muniruddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study aimed to determine the effect of firm size, managerial ownership, foreign ownership, and the board of commissioners independent of Corporate Social Responsibility Disclosure in manufacturing companies listed in Indonesia Stock Exchange 2010-2014. This study uses the annual report as the data with a sample of the company is 26 observation data. Selection of research sample was conducted using purposive sampling nonprobability form. The annual reports used were obtained from sites www.idx.co.id. Data processing was done by using multiple linear regression and has been qualified classical assumption test. The results showed that the variable size of the company, positive and significant impact, while the variable managerial ownership, foreign ownership and independent commissioners significant negative effect on the Corporate Social Responsibility Disclosure. R-square value of 13.4% indicates that 13.4% of corporate social responsibility disclosure can be explained by the independent variables used in this study, while the remaining 86.6% is explained by other factors not be used as an independent variable in this study